Improving the Utilization of Human Papillomavirus and Cervical Cytology Co-testing for Cervical Cancer Screening in an Obstetrics and Gynecology Resident Clinic - Yoshino, Kurt (Hawaii J Med Public Health, 2015)
Human Papillomavirus (HPV) testing in combination with cervical cytology (HPV co-testing) has been recommended for cervical cancer screening for women 30 to 65 years of age. In several studies, HPV co-testing increased sensitivity for detecting high grade dysplasia and resulted in cost-savings. This retrospective cohort study assessed the prevalence of HPV co-testing in an obstetrics and gynecology resident clinic before and after a brief educational intervention which was designed to reinforce current cervical cancer screening recommendations. The intervention consisted of a short presentation that was given to all residents and medical assistants in October 2011. The proportion of women age 30–65 years of age who had cervical cancer screening with HPV co-testing as compared to cervical cytology alone was compared before and after the intervention using chi-square tests. The goal of the intervention was to increase the percentage of patients receiving co-testing from 0.5% to 7.8%. Each arm (pre- and post-intervention) required 130 subjects to achieve 80% power with a significance of P = .05. No significant differences in demographics including age, insurance type, and cytology were noted. HPV co-testing increased from 0% to 55% (P < .001). Of the 72 subjects who had co-testing, 58 (80%) will not need cervical cancer screening for another 5 years. HPV co-testing represents an underutilized cervical cancer screening modality for women 30 years and older. This brief educational intervention, adaptable to any clinical setting, significatnly increased co-testing at the clinical site.